A comparison of wound healing between a skin protectant ointment and a medical device topical emulsion after laser resurfacing of the perioral area - Sarnoff, Deborah S. (Journal of the American Academy of Dermatology, 2011)
Currently, there is no standard of care for postlaser resurfacing treatment of the face. Ideally, treatment should speed re-epithelialization and reduce downtime, with minimal irritation. This study compared the wound healing efficacy and safety of Aquaphor Healing Ointment (AHO) (Beiersdorf Inc, Wilton, CT) and Biafine Topical Emulsion (BTE) (OrthoNeutrogena, Los Angeles, CA) treatment after laser resurfacing of the perioral area. In this double-blind, split-face study, 20 subjects with perioral rhytides received fractional carbon dioxide laser resurfacing. AHO and BTE were applied to opposite sides of the face 4 times daily after the resurfacing procedure. Clinical grading of erythema, edema, epithelial confluence, crusting/scabbing, subjective irritation, and general wound appearance were assessed using 5-point scales on days 2, 4, 7, and 14. Subjects ranked the two treatment sites daily as to which side of their face looked better. AHO resulted in significantly less erythema (days 2 and 7) and crusting/scabbing (days 2, 4, and 7) and higher epithelial confluence (day 4) than BTE ( P ≤ .042). Subjective irritation assessments demonstrated significantly less stinging, itching, and tightness at day 2 and tightness at day 7 with AHO than with BTE ( P ≤ .049). General wound appearance was graded significantly higher for AHO on days 2 and 7 ( P ≤ .049). Significantly more subjects preferred AHO to BTE ( P ≤ .046). This was a small study in a homogenous population of white women. AHO exhibited superiority to BTE in several wound healing parameters and in overall wound condition.